Benedicto XVI y San Agustín de Hipona: Magisterios de ayer para el mundo de hoy. Influencia de San Agustín en Benedicto XVI (primera parte) = Benedict XVI and Saint Augustine of Hippo: Magisterium of yesterday for today’s world. Influence of Saint Augustine on Benedict XVI (first part) - Rey, Pablo Antonio Morillo (Isidorianum, 2016)
There is no doubt at all that Saint Augustine of Hippo is the Father of the Church who has had the greatest influence, —and still has— , on the Church, as well as on plenty of Popes. One of them, Pope Benedict XVI, will become the objective and the subject of our project of investigation, a survey which will be completed progressively and will be published in the form of an ongoing collection of articles. In relation to this, our attention will be focused on certain documents, such as Encyclicals, Apostolic Exhortations and motu propio documents. With all of them, the reader will be able to find out, much more easily, the explicit and implicit Augustinian influences contained within those pontifical documents. That is why we suggest the reader a peaceful reading, a paused thinking and a personal enrichment, taken from the texts., Sin duda alguna, es San Agustín de Hipona el Padre de la Iglesia que mayor influjo ha ejercido —y continúa ejerciendo— en esta, así como en numerosos Pontífices. Uno de ellos, Benedicto XVI, será el objeto de nuestro estudio investigativo, estudio que —progresivamente— irá siendo completado, así como viendo la luz, a través de una serie de artículos. En este caso, serán ciertos documentos tales como Encíclicas, Exhortaciones Apostólicas y documentos en motu proprio, los que centren toda nuestra atención. En estos, el lector podrá descubrir con una mayor fluidez cuántas influencias agustinianas, directas o indirectas, se hallan reflejadas en dichos documentos pontificios. Es por ello que invitamos a su lectura pausada y detenida reflexión.